Updates in Sertoli Cell-Mediated Signaling During Spermatogenesis and Advances in Restoring Sertoli Cell Function - Ruthig, Victor A.; Lamb, Dolores J. (Frontiers in Endocrinology, 2022)
Since their initial description by Enrico Sertoli in 1865, Sertoli cells have continued to enchant testis biologists. Testis size and germ cell carrying capacity are intimately tied to Sertoli cell number and function. One critical Sertoli cell function is signaling from Sertoli cells to germ cells as part of regulation of the spermatogenic cycle. Sertoli cell signals can be endocrine or paracrine in nature. Here we review recent advances in understanding the interplay of Sertoli cell endocrine and paracrine signals that regulate germ cell state. Although these findings have long-term implications for treating male infertility, recent breakthroughs in Sertoli cell transplantation have more immediate implications. We summarize the surge of advances in Sertoli cell ablation and transplantation, both of which are wedded to a growing understanding of the unique Sertoli cell niche in the transitional zone of the testis.